A Swiss collaborative exercise for Disaster Victim Identification (DVI): Covering situations with different levels of complexity. (October 2021) - Gehrig, Christian; Delémont, Séverine; Comte, Jennifer; Hicks, Tacha; Basset, Patrick; Grosjean, Frédéric; Dion, Daniel; Cossu, Christian; Bottinelli, Michel; Hecht, Mirco; Sulzer, Andrea; Voegeli, Pamela; et al.
Abstract: The identification of victims of a disaster (DVI) requires the collaboration of different specialists. Within a DVI context, DNA analyses often play an important role. Consequently, forensic genetic laboratories should be prepared to cope with DVI situations, as this can involve large-scale DNA profile comparisons. Six forensic genetic laboratories from Switzerland participated in an exercise where supposedly a plane had crashed. The goal of the exercise was to monitor participants use of dedicated software with ground truth cases and to make them aware of the existence of particular situations that may occur in real cases. For assigning the value of the comparison of the DNA profiles, all participating laboratories used the DVI module of Familias v3.2. 1 In addition, one of the 6 laboratories used the Pedigree Searcher from CODIS v7.0. The data (AmpFlSTR® NGM SElect™ profiles) were generated to challenge the participating laboratories: cases with first, second degree biological parents, mutation events, as well as non-paternity cases were included. This study shows that the majority of the participants used the software in an appropriate way. However, a few misleading conclusions were detected for the most challenging situations. These errors belonged to one of the following categories: false pedigree, false association using the higher LR, misleading contextual information (false paternity) and not clustering family members. Specific recommendations are provided in order to reduce misuse of the software and the risk of misinterpretations by using all the relevant information. Highlights: Six forensic genetic laboratories from Switzerland participated in an exercise involving a simulated plane crash. The main goal was to experiment a DVI situation with a large amount of DNA data and to be aware of the common pitfalls. In the identification process one should combine the DNA evidence with the non-genetic evidence.